Restructuring the European Business Enterprise: the European Commission’s recommendation on a new approach to business failure and insolvency - Eidenmüller, H; Van Zwieten, K (Springer Verlag, 2016)
Two events are currently changing the landscape for business restructurings in the European Union: the ‘Restructuring Recommendation’ (RR) of the European Commission, issued in 2014, and the 2015 recast of the European Insolvency Regulation (EIR). In this paper, we critically review the RR and put it into the context of the reform of the EIR. We find that the recast EIR and the RR do not dovetail perfectly—a restructuring proceeding as proposed by the RR would not necessarily be within the scope of the recast EIR; we also suggest that, in any case, the EIR is not optimally designed to facilitate restructurings, given its treatment of secured creditors. Regarding the regulatory approach pursued in the RR, the Commission rightly pushes towards harmonisation with respect to Member States’ restructuring regimes—regulatory competition is not a sensible regulatory alternative in this area. However, we criticise both the methodology and scope of the harmonisation proposal of the RR: sketchy minimum harmonisation of restructuring rules leaves huge potential for residual diversity in Member States’ restructuring laws, and the Commission’s narrow focus on restructuring proceedings ignores several aspects of the complicated interaction between the Member States’ formal insolvency laws and the restructuring mechanism proposed. Further, we disagree with the substantive recommendations for Member States’ restructuring laws suggested by the RR: they wrongly require financial difficulties or a likelihood of insolvency as an entry test for the recommended restructuring proceeding, and the process appears susceptible to abuse by sophisticated financial investors—it does not provide for the mandatory appointment of a supervisor and allows significant curtailments of creditor rights without sufficient safeguards in place. Instead, we propose an efficient debtor-in-possession (DIP) regime as an alternative that could be initiated regardless of a firm’s solvency, provided that it is economically viable and that the filing is not abusive.